Psychological burden and resilience factors in patients with Alveolar Echinococcosis: a cross-sectional study - Nikendei, Christoph; Greinacher, Anja; Junghanss, Thomas; Stojković, Marija (PLoS neglected tropical diseases, 2019)
Background Alveolar echinococcosis (AE) is a parasitic zoonosis resembling malignancy due to its clinically silent infiltrative growth, predominately in the liver. The comorbid psychological burden and fear of disease progression in AE patients have hardly been examined to date. The aim of this study was to evaluate depression, anxiety, quality of life, and fear of disease progression in AE patients. Methodology/Principal findings In a cross-sectional study, n = 57 AE patients were invited to report on depression (PHQ-9), anxiety (GAD-7), somatic symptom load (SSS 8), trauma symptoms (PTSS-10), quality of life (SF-12) and on fear of disease progression (FoP-Q-SF) using validated psychometric instruments. Furthermore, attachment style was assessed (RQ-2). N = 47 patients completed the questionnaires (response rate 82.5%). Depression, anxiety, and somatic symptom load were above norm sample means, while physical quality of life was below norm sample means. Existing traumatic symptoms were comparable to those in cancer patients, while fear of disease progression even exceeded cancer patient scores. Patients with a secure attachment style showed less pronounced psychological burden than patients with other attachment styles. Adequate, guideline-based depression and anxiety treatment was very rarely installed. Conclusion/Significance The present study revealed remarkable levels of psychological burden in AE patients. In our study sample, we discovered high depression and anxiety levels, a significant reduction of physical quality of life, and fear of disease progression. These results show how important it is for AE patients to be thoroughly assessed with regard to psychological symptoms and mental disorders so that those in need can receive sufficient psychosocial support and treatment according to official guidelines.
Gesehen am 12.11.2019